Ethylene inhibitor aminoethoxyvinilglycine on glomerella leaf spot in apple cultivar 'Royal Gala' Inibidor de etileno aminoetoxivinilglicina sobre a mancha foliar de 'Glomerella' na cultivar de macieira 'Royal Gala' - Kuhnem Jr. P.R.* (2011)
Aqueous solution of Aminoethoxyvinylglycine (AVG) has been commercialized in Brazil as ReTain™C, 15% mainly as a potent inhibitor of ethylene biosynthesis by prevention of pre-harvest abscission and ripening of apple fruits. The effect of the product was evaluated during the 2007-08 and 2008-09 crop seasons in edafoclimatic conditions of Santa Catarina upland. Plants of 'Royal Gala' cultivar were sprayed with ReTain™C, four weeks before the first commercial harvest at doses of 0; 62,5; 125, and 250mg a.i L -1. The incidence and severity were quantified weekly in 100 leaves distributed in four branches with 12 replications and assessed the area under the incidence -I and severity -S disease progress curve (AUIDPC and AUSDPC) of Glomerella leaf spot (GLS). The AUIDPC and AUSDPC were significantly higher after AVG application and although there was no significant difference between 125 and 250mg a.i L -1 doses in both 2007-08 and 2008-09 crop seasons. In general, the symptoms of GLS (e.g. chlorosis, necrosis) increased between the fourth and eighth week after application.